Evaluation of Socio-demographic and Lifestyle Factors Among Subtypes of Irritable Bowel Syndrome - Chowdhury, Sadia Rahman; Safwath, Syed Alamgir; Ghosh, Dilip Kumar; Mahmuduzzaman, Mohammad; Saha, Madhusudan; Alam, Md Jahangir; Choudhury, Muiz Uddin Ahmed (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorder with absence of organic damages to the intestine. The pathophysiology of IBS is still not completely understood, but in some cases psychological disorders may affect the onset and outcome of IBS. Some studies have found disparities between subtypes of irritable bowel syndrome (IBS) regarding socio-demographic characteristics and lifestyle factors. Methods: This cross-sectional study aimed to investigate whether there are differences in sociodemographic and lifestyle factors including smoking and physical activity between the subtypes of IBS. The study was performed on outpatients diagnosed as irritable bowel syndrome (from January 2015 to December 2015) in Dhaka Medical College Hospital and Shaheed Suhrawardy Medical College Hospital in Dhaka. A total of purposively selected 208 diagnosed IBS patients were interviewed by semi-structured questionnaire in which subtype of irritable bowel syndrome were measured by Rome-III criteria regarding stool consistency. Results: Mean age of the respondents was 32.3 (+ 10.32) years and majority of them were male (77%), married (66.8%), educated up to secondary level (35.6%), labour (skilled and unskilled) (30%), non- smoker (67.3%) and HEPA (health enhancing physical activity) active (65.9%). Diarrhea predominant irritable bowel syndrome (50%) was found the most common subtype among the irritable bowel syndrome respondents followed by mixed type irritable bowel syndrome (42%) and constipation predominant irritable bowel syndrome (8%) There were no statistical differences found between constipation predominant irritable bowel syndrome ( IBS-C), Diarrhea predominant irritable bowel syndrome (IBS-D), and mixed type irritable bowel syndrome (IBSM) patients regarding to socio-demographic characteristics and lifestyle factors (P<0.05). Conclusion: Our study concluded that there are no different socio-demographic and lifestyle characteristics between IBS subtypes. J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 6-9